A use-wear analysis of wood technology of patagonian hunter-gatherers: The case of Cerro Casa de Piedra 7, Argentina - Caruso, Laura Lihue (2015)
In the Patagonian archaeological record, the preservation of wooden artefacts is very restricted. Functional analysis of lithic artefacts is a way to get a better understanding about the use and consumption of the wood. El análisis tecnológico y funcional de artefactos de madera tiene por objetivo representar el proceso de producción y uso de estos objetos, centrándose en las etapas: desde la adquisición de la materia prima hasta la obtención del producto final. Technological and use-wear analyses are applied in order to reconstruct the production processes of the wooden artefacts, from the raw-material supplying to the production of the finished tools.In this paper we present the results of a taxonomical and techno-functional analysis of the traces preserved on the surface of the two wooden artefact retrieved from layer 17 (9390±40 C14 yearsBP) and layer 6 (5310±110BP) at the site of Cerro Casa de Piedra 7 (province of Santa Cruz, Patagonia, Argentina). The interpretation of these two objects is complicated due to the absence of ethnographical references and the lack of similar archaeological findings in Patagonian hunter-gatherers sites. However, through the observation of the use-wear traces it is possible to reconstruct part of the manufacturing process and advance hypothesis on their mode of employment. Due to the distribution of the wears and the mineral-organic residues identified on the surfaces, it is proposed that one of the wooden artefact was probably used for rock-art production.